Good Governance and School Administration - ชยธมฺโม พระสรรชัย (Journal of Educational Review Faculty of Education in MCU, 2018)
Administration and Management of schools should be applied with good governance principles to lead work and administration to great success. The principles of good governance are based on legal principles, moral principles, transparency, responsibility, participation, and worthiness. The administration integrated with good governance principles is recognized as the best practice leading organizations to effective development.